Tempos cotidianos de professoras/es fora da escola: outras histórias - Geovani de Jesus Silva (2014)
This work analyses the configurations of basic education schools teachers and their time out-side school, taking into account aspects from the socio-historical processes that constitute them. The research has as its assumption that the notion of time is a historical and cultural construction, which translates a symbolic synthesis related to how life happenings, nature, world, events flow (Norbert ELIAS, 1998), which involves, among other aspects, rhythms, durations and how the memory, remembrances and individuals and groups projections work throughout their individual and collective memories. Moreover, it deals with experience and learning. Among social periods of time, this study focuses on free time, which is understood as those free periods from any professional demands and paid employment. Among those pe-riods, there are previous, subsequent and interstices ones of working activities as well as short and medium periods of interruption, such as holydays, weekends, vacation, respectively. Those would be occasions when individuals could experience activities chosen by them, in order to have satisfaction, fulfill their personal needs, among other alternatives they may have in their everyday life.Some actions are included in free time such as leisure activities, resting periods, regeneration, biological needs, taking care of themselves, among other actions which vary from individual to individual and from one social group to another (Erich WEBER, 1969; Norbert ELIAS and Eric DUNNIG, 1992). The study of teachers time outside school in principle, it is not their free time in fact is little explored by Brazilian educational re-searches, one of the main reasons why this work discusses the problem.It intends to contribute and bring to light the problem of scarce free periods of timein teachers everyday life, a phe-nomenon which affects their bodies, their minds, their performances at work and other places. Besides, it is a phenomenon which is prejudicial, causes tensions, conflicts and has terrible consequences to both human and existential condition of these professionals. Such problems rose during the research. The research is circumscribed in a sociological perspective Sociol-ogy of Work, Sociology of Professions and Sociology of Time fields which has achieved a relative consolidation in sociological literature. The subjects of the research were both public and particular teachers of Porto Seguros (Bahia, Brasil) basic education schools, who we investigated through questionnaires, taped individual semi-structured interviews and focal groups.In addition, in order to gather information, we usedas a methodological procedureelectronic mail/messages, taking into account that the field research occurred from January to December 2013. In this sense, the text is organised in three analytical parts: the first one contains a general spectrum of teachers periods of time, theoretically periods of free time, in other words, it is elaborated a panorama of theirdoings and livings in their free time outside school.The second part discusses their behaviours in their free time, that is, the pro-cesses of suspension, compensation and regeneration (Erich WEBER (1969)). The third part attempts to understand the challenges, tensions and conflicts of teachers everyday periods oftime outside school as well as strategies and tactics used by those teachers in order to con-ciliate working periods with their free times.Considering these teachers lives and stories, among the researchs findings, it was clear that they live subsumed and under stress, conflict-ed with their scarce free time and the overlapping of endless work. Their periods of time out-side school, which would be considered free time, transmute in periods of time to do another tasks.It is concluded that these teachers everyday periods of time outside school cannot be considered free time per se because they correspond to another types of work. It is an experi-ence marked by labour activity as well as challenge of articulating several situations, mo-ments, durations and rhythms of everyday life in order to accomplish teaching workload. Mainly, it is a temporal setting related to historical condition of contemporary working times, with its developments in school and teaching temporalities, in which teachers are dealing with time, time that shapes their way of living, in present and past times, with individual and col-lective historical moments.